Innovative Approaches to Teaching English as a Second Language: A Comprehensive Analysis - Martan, Viven (Majapahit Journal of English Studies, 2025)
This article explores innovative approaches to teaching English as a second language (ESL) in diverse educational contexts. By reviewing current literature, analyzing research methodologies, and discussing findings, this study aims to provide educators with practical strategies to enhance language acquisition. The article concludes with recommendations for future research and pedagogical practices.